Alymphoid cystic thymic dysgenesis - FOXN1 gene mutation: a rare case report of two siblings - Sohail, Abdus Subhan; Krishnamurthy, Vidya; Sanikam, Hareesh; Kariyappa, Pushpalatha; Rao, Udayakumar Seetharam (International Journal of Contemporary Pediatrics, 2020)
Alymphoid cystic thymic dysgenesis is a severe combined immunodeficiency (SCID) syndrome caused b y a mutation in fork head box N1 gene (FOXN1) on chromosome 17. It is a transcriptional factor regulating the development, differentiation and function of thymic epithelial cells; maintaining T-lineage progenitors in bone marrow; promoting terminal differentiation of epithelial cells of hair follicles. Mutation in FOXN1 is known to cause a rare disorder characterized by rudimentary thymus gland (primary lymphoid organ for T-cell differentiation), T-cell immunodeficiency, congenital alopecia totalis and nail dystrophy. Here we report two affected siblings from a non-consanguineous family with similar features of alopecia totalis, nail dystrophy and failure to thrive. The first child was a 7-month-old female baby, with history of two hospitalization in the past for lower respiratory tract infection, had left axillary lymphadenopathy (BCG adenitis), alopecia totalis, nail dystrophy and hepatosplenomegaly. Bronchoalveolar lavage secretion was positive for Mycobacterium tuberculosis and Pneumocystis carinii pneumonia by gene Xpert and polymerase chain reaction respectively. Immunodeficiency panel workup revealed combined T cell and B cell immunodeficiency, genetic analysis by whole exome sequencing revealed recessive missense mutation in exon 6 of FOXN1 gene on chromosome 17. Due to lack of sufficient literature it was reported as variant of unknown significance and to establish its clinical significance the carrier status of both the parents was established. Second child presented to us at 3 months of age, also had similar phenotypic features and on evaluation had very low lymphocyte subset count however mutational analysis could not be done in this child due to parent’s denial. Hence, we conclude this child also was affected.